The effectiveness of learning portfolios in learning participation and learners' perceptions of skills and confidence in the mother of preterm infant. (July 2018) - Cheng, Yi-Chuan; Chen, Li-Li; Chang, Yu-Shan; Li, Tsai-Chung; Chen, Ching-Ju; Huang, Li-Chi
Highlights: We developed the Preterm Infant Care Learning Portfolio (PICLP), to assist mothers with preterm infants in learning baby care before discharge. The PICLP improved the learners' participation which was double times of practicing than control group in learning new skills. The PICLP could be an effective teaching strategy for patient education, enhancing the awareness of learning needs and participation in leaning skills. Abstract: Objective: The purpose of this study was to investigate the effectiveness of preterm infant learning portfolios in enabling mothers to develop infant care knowledge and skills, as well as confidence in their abilities. Design: This study used a quasi-experimental design. Setting and participants: The sample consisted of 52 mothers with preterm infants recruited at a neonatal intermediate unit of a medical centre in central Taiwan. Among those, 26 participants in the control group received regular health education and 26 participants in the experimental group received learning portfolios and regular care. Intervention: The Preterm Infant Care Learning Portfolio (PICLP) is a semi-structured learning portfolio which was provided by nurses. Intervention started with 15 min of instructions on how to use PICLP, including a list of learning task and methods of self-assessment. Follow-up sessions of 5–10 min were conducted after each learning task. The frequency of learning skills could be adjusted depending on participants' learning needs. Measurements: Self-administered questionnaires regarding knowledge of and skills in preterm infant care and maternal confidence were used to evaluate the effectiveness of the intervention; the questionnaires were conducted before the intervention, 1 day before discharge and 1 month after discharge. We also tracked the frequency with which participants attended instructional sessions before discharged. Findings: Mothers' preterm infant care knowledge and skills and confidence improved in both groups after the intervention. The experimental group showed greater improvement than the control group by post-test 2; there was no statistical difference between groups at 1 day before discharge and 1 month after discharge. However, participants in the experimental group came for instructional sessions on baby care for more frequently than the control group. The frequency of learning sessions attended was a predictor of improved scores of the skill assessment before discharge. Conclusions: Both programmes led to improvements in preterm infant care knowledge and skills and maternal confidence. Giving mothers learning portfolios appears to stimulate significantly greater participation in hospital-based instructional programmes, which should in turn lead to greater long-term retention of learning. The learning portfolios may have an additional benefit in promoting acquisition of care abilities for mothers with preterm infant before hospital discharge and application of these abilities at home. Implication for practice: At-home care for preterm infants requires specialized care skills and confidence. Learning portfolios can be used as an effective learner-centred strategy for teaching these health care abilities.